The Paradox of Keeping Exotic Animals as Pets - David Fernández, Rafael Andrés; Richards, Ngaio; San Andrés Larrea, Manuel Ignacio; Briones Dieste, Víctor; Brufao Curiel, Pedro (Studia Ecologiae et Bioethicae, 2025)
In the European Union (as elsewhere), there are many activities that involve animals and which must, as such, be subject to regulation. These include trade, livestock farming, fishing or for the purpose of environmental protection. Some of these regulations also cover the definition of “pet animals” which includes both domestic and exotic pets- whether from the natural environment (wild animals) or bred in captivity from originally wild animals. Species that have adapted to or undergone a domestication process present a series of characteristics that are more favorable for or conducive to coexistence with humans. This article explores whether exotic species should be viewed as “pets,” based on – by their very nature - being inherently incompatible with domestication, including their habitat/living requirements. In addition, it raises issues around, and rationale or drivers of, the practice of trading and acquiring exotic species as pets, when there is the alternative of keeping a domestic animal for this purpose instead.